The World's Largest Humanitarian Agency The Transformation of the UN World Food Programme and of Food Aid - Shaw, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book focuses on the transformation of the WFP into the world's largest humanitarian agency, providing an in-depth account of responses to increasingly large and complex natural and man-made disasters. It examines food aid and looks to the new modalities that are required to make food more available to those in dire need.
Keywords: International economics; Development economics; Economic history; Environmental economics; International Economics; Development Economics; Economic History; Environmental Economics